Elderly Satisfaction on Chronic Disease Management Program at Public Health Center, Bandung City, West Java, Indonesia - James Maladi Akbar; Sharon Gondodiputro; Ardini Saptaningsih Raksanagara (Faculty of Medicine Universitas Padjadjaran, 2020)
Objective: To identify the satisfaction level of the elderly on the health services provided by The Chronic Disease Management Program (prolanis) at the Public Health Center (puskesmas).Methods: A descriptive quantitative study with a cross-sectional approach had been carried out to 112 elderly from 8 puskesmas in Bandung City, West Java, Indonesia. This study was conducted from August until November 2019. The variables in this study were 5 dimensions of the SERVQUAL. The collected data were analyzed using percentages and the Importance-Performance matrix.Results: The satisfaction level of the elderly on the health services provided by the prolanis was 92%. The dimension that has the highest satisfaction level was the assurance dimension (94,6%) and the lowest one was the tangibles dimension (84,8%). The result of the importance-performance matrix showed that assurance, responsiveness, and empathy dimensions needed to be maintained to reach the patient’s satisfaction. Conclusions: The elderly satisfaction on the health services provided by the prolanis is high in every dimension of the SERVQUAL.